MADE IN BRAZIL: CONSPIRACY THEORY AND THE FLOW OF INFORMATION IN ONE-TO-ONE WHATSAPP CONVERSATIONS - R. Rosa, Fernanda (Revista Prelúdios, 2021)
This essay aims to shed light on the multiple and complex ways that information flows among individuals in times of intense use of digital platforms. Based on actor-network theory, it unveils largely unknown communication processes about the controversial death of the Brazilian Supreme Court Justice, Teori Zavascki in 2017 that occurred in closed conversations in which the author was part. Analyzing primary data, the essay discusses the signs of authority that allow for non-verified or fiction pieces to circulate as if they were news pieces, enabling conspiracy theories to take form. The essay defends that mutual responsibility in building the narrative with peers within a likeminded groups, and “translation” processes in which sender and information merge their characteristics to create trust are important factors to understand this phenomenon. Furthermore, in discussing news as cultural artifacts, the essay also raises reflections of the limits of framing this phenomenon as fake news, which artificially oppose what is “real” and “fake” disregarding cultural dynamics at stake.